Análisis para el Diseño de una Base de Datos para el Departamento de Vinculación con la Sociedad de la Universidad Técnica de Babahoyo - Plaza Nicola, Angye Aurora (2017)
The present project arises from the need to obtain a better organization in the information, so it is proposed to develop an analysis for the design of a database for the Department of Linkage with the society of the Technical University of Babahoyo. Linkage with society performs a vital role for the different Faculties, by which the University contributes with its methodological theoretical contingent to the solution of practical problems of society. It is one of the most sensitive factors in assessing and appreciating the relevance of the University and its environment, and the reality in which this interaction takes place has many factors that, with different origins and interests, affect the reality that must be improved in its aspects. At the moment the Department of Linking does not have any type of system which allows to process the information in a suitable way, due to this inconvenience its files are elaborated in computer packages utilas and stored in the computer desktop. Due to not having ordered the information this generates difficulty when searching the information on the different projects that exist, causing in this way a loss of time.